O nonsense no diálogo palavra e imagem em Alice no País das Maravilhas e Através do Espelho, de Lewis Carroll - Simões, Selma (2013)
The aim of this dissertation is to study nonsense in dialogue incorporated in the narrative process, in Lewis Carroll s masterpieces, Alice s Adventures in Wonderland and Through the Looking-Glass, with the purpose to observe the effects of the lack of coherent meaning in writing and rewriting through the characterization art illustration. In reading those works we verified how two ways of narrating/presenting were brought together by Nineteenth-century through the mediation of the logic of nonsense. Such a connection introduced certain markers in the discourse, and these work out a transposition form the logical to the illogical, in both verbal and non-verbal communication. Such an operation produced events of language, of inversion, and of semantic meaninglessness or emptying of meaning, which were interpreted by the readers- illustrators, as modes of artistic exercise by Lewis Carroll, John Tenniel modern and contemporary illustrators that make up the focus of our texts in the analysis and interpretation. In order to understand mediation of the nonsensical word and recognize it in the modes of creative interpretation exercise, we propose three hypothesis which were expectedly demonstrated and interpreted by resorting the multiple theoretical supports. The first demands the correlation and equivalence between the verbal and visual enunciates counterpoising each other in the communication process. The second indicates the perceptive, semantic and artistic markers of differences present in verbal and visual enunciates as indexing units dialogue replies. The last situates word and image as mediated by nonsense devoid of time-frontiers, pushing Carroll s narratives towards a polysemy of values and senses by means of the art to characterize illustration as works of an infinite significance